2021
DOI: 10.3390/ijms22126535
|View full text |Cite
|
Sign up to set email alerts
|

The Journey of DDR1 and DDR2 Kinase Inhibitors as Rising Stars in the Fight Against Cancer

Abstract: Discoidin domain receptor (DDR) is a collagen-activated receptor tyrosine kinase that plays critical roles in regulating essential cellular processes such as morphogenesis, differentiation, proliferation, adhesion, migration, invasion, and matrix remodeling. As a result, DDR dysregulation has been attributed to a variety of human cancer disorders, for instance, non-small-cell lung carcinoma (NSCLC), ovarian cancer, glioblastoma, and breast cancer, in addition to some inflammatory and neurodegenerative disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 163 publications
1
42
0
3
Order By: Relevance
“…Additionally, we demonstrated that the inhibition of proteins related to cell cycle and migration can be useful in targeting leukemic expansion in vivo . Inhibitors targeting discoidin domain receptor 1 (DDR1), BAY-826 and DDR-IN-1 are promising hits as DDR1 inhibition has potential in cancer therapy ( Elkamhawy et al, 2021 ; Berestjuk et al, 2022 ). Moreover, DDR1 therapeutic targeting in vivo was not yet characterized for the treatment of myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we demonstrated that the inhibition of proteins related to cell cycle and migration can be useful in targeting leukemic expansion in vivo . Inhibitors targeting discoidin domain receptor 1 (DDR1), BAY-826 and DDR-IN-1 are promising hits as DDR1 inhibition has potential in cancer therapy ( Elkamhawy et al, 2021 ; Berestjuk et al, 2022 ). Moreover, DDR1 therapeutic targeting in vivo was not yet characterized for the treatment of myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we demonstrated that the inhibition of proteins related to cell cycle and migration can be useful in targeting leukemic expansion in vivo . Inhibitors targeting discoidin domain receptor 1 (DDR1), BAY-826 and DDR-IN-1 are promising hits as DDR1 inhibition has potential in cancer therapy (Berestjuk et al, 2022; Elkamhawy et al, 2021). Moreover, DDR1 therapeutic targeting in vivo was not yet characterized for the treatment of myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed targeting DDR1 as a therapeutic strategy against resistance to BRAF and MEK inhibitors ( 81 ), further confirming the significance of our findings, which suggest an unprecedented role of the interactome of DDR1, BCR, and ABL1 proteins with EGFR-ERBB2-4 signaling in tumor progression. The only FDA-approved drugs currently available for DDR1 and BCR/ABL proteins are the BCR-ABL family of multi-tyrosine kinase inhibitors; however, DDR1- and BCR-ABL-specific compounds are constantly being developed ( 82 , 122 ), and a combination of DDR1-, BCR-ABL1-, and EGFR/ERBB2-4-specific drugs could co-operate, synergize, and open a new paradigm for future cancer therapeutics.…”
Section: Discussionmentioning
confidence: 99%